2019
DOI: 10.1039/c9nr03701b
|View full text |Cite
|
Sign up to set email alerts
|

Broadband nonlinear absorption properties of two-dimensional hexagonal tellurene nanosheets

Abstract: Low saturable intensity, large TPA coefficient and the absorption cross-section demonstrate that tellurene is an advanced broadband nonlinear absorption material and has potential applications in the nonlinear optics field, especially in the infrared band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…2(b)]. Further increasing the laser intensity to tens of GW∕cm 2 , it exhibits a clear RSA behavior for open Z-scan measurement, which is consistent with previous reports of bulk InP [38]. From the obtained saturation intensity, the modulation depth, and the nonsaturable loss, it shows great potential for InP NWs to work as a saturable absorber for the generation of pulsed (e.g., passively Q-switched, mode-locked) lasers.…”
Section: B Nonlinear Optical Absorption Propertiessupporting
confidence: 89%
“…2(b)]. Further increasing the laser intensity to tens of GW∕cm 2 , it exhibits a clear RSA behavior for open Z-scan measurement, which is consistent with previous reports of bulk InP [38]. From the obtained saturation intensity, the modulation depth, and the nonsaturable loss, it shows great potential for InP NWs to work as a saturable absorber for the generation of pulsed (e.g., passively Q-switched, mode-locked) lasers.…”
Section: B Nonlinear Optical Absorption Propertiessupporting
confidence: 89%
“…In 2017, Zhang et al [114] firstly have been focus on the environmental stability of two-dimensional Te, and they found that Te had a high carrier mobility. In 2019, Xu et al [116] first used Z-scanning technology to explore the broadband nonlinear absorption characteristics of Te.…”
Section: Mono-elemental Analogs 321 Tellurenementioning
confidence: 99%
“…The above two processes have been applied to the fields of mode-locked lasers and laser protection with excellent optical limiting performance, respectively. [17][18][19][20][21][22] The above nonlinear absorption mechanisms can also be dominated by the absorption cross-section-when the excited state absorption cross-section is smaller (or larger) than the ground state absorption cross-section, the sample will exhibit SA behavior (or RSA behavior). [23][24][25][26] In addition, the responsivity and modulation depth of nonlinear photonic devices are affected by the lifetime of carriers at virtual levels.…”
Section: Introductionmentioning
confidence: 99%